Queer Linguistics: Exploring Pragmatic Strategy within Gay’s Language on Online Dating Apps - Istighfarna, Hanif Azhar; Setiawan, Slamet (New Language Dimensions, 2024)
A play in meanings can be found within an internal interaction of a secretive and concealed community. In Surabaya, queer individuals, particularly gay men, employ secret codes within their language as a defensive measure against conservative societal norms. The primary strategy of this coded language involves the selection of specific vocabulary and the nuanced meanings embedded within it. Many MSMs (men who have sex with men) utilize these vocabularies for communication, primarily through online dating apps. This study aims to uncover the registers within the gay community and explore how their meanings correspond with their literal meanings in the English language. The research employs a case study method of qualitative approach and applies Leech’s seven types of meaning theory (1981) for analysis. The findings reveal that gay registers convey connotative, reflected, social, and collocative meanings. Connotative meaning is the most commonly used, followed by reflected, collocative, and social meaning. Connotative meanings are frequently employed because the gay community assigns codes to various concepts based on their real-world references. The study sheds light on how queer communities, particularly MSMs in Surabaya, use coded language as a tool for navigating conservative societal pressures. This highlights the adaptability of marginalized groups in protecting their identities, emphasizing the importance of language as valid form of expression and resistance. Future research could expand to other regions with similar or differing cultural contexts, allowing for comparative analysis of coded language usage among MSMs in various conservative environments and providing a more comprehensive understanding of the phenomenon.